Model Quantum Learning dalam Pembelajaran Bahasa Indonesia yang Nyaman dan Menyenangkan - Sumartini, Sri (Lembaga Sosial Rumah Indonesia, 2023)
This study aims to create comfortable and enjoyable learning Indonesian and improve learning achievement in class 1B MIN 2 Sleman. This research is class action research with research subjects of class 1B students at MIN 2 Sleman for the 2021/2022 academic year with a total of 28 students. Data collection was carried out using observation sheets, daily journals, unstructured interviews, and documentation. Data analysis was carried out in a qualitative descriptive manner. The results showed that the quantum learning model with the language game method is a learning method that can create a comfortable and enjoyable learning atmosphere, as evidenced by an increase in the results of observations of learning activities, namely in cycle 1 the percentage of comfortable and enjoyable learning reached a percentage of 68.40% while in cycle II it reached 79.15%. There has been an increase of 10.75% and can improve the learning achievement of class IB students where in the first cycle the average value of learning outcomes is 75, the second cycle the average value is 87.